Context and culture in language teaching and learning - Byram, Michael; Grundy, Peter (Languages for intercultural communication and education, 2003)
This work addresses the significance of the relationship between the aims and methods of language teaching and the contexts in which it takes place. It considers the implications of this for the ways in which we research language teaching, and presents the results of research and development work.